Curious case of CGRaBS J0211+1051: observational evidence of the lepto-hadronic origin of high-energy emission? - Chandra, Sunil; Kushwaha, Pankaj; Goswami, Pranjupriya; Zacharias, Michael (The astrophysical journal, 2025)
We present an extensive analysis of the multiwavelength data of the low-synchrotron-peaked BL Lac object CGRaBS J0211+1051 that have been gathered over more than 10 yr with many observatories. Two major γ-ray flares have been observed during the Fermi era: one in 2011 January and the other in 2019 June. During these events, CGRaBS J0211+1051 was also bright in other energy bands. On the other hand, there are also examples of optical activity that do not exhibit any comparable γ-ray variability. Here, we study the temporal and spectral characteristics of the object in an attempt to understand the emission mechanisms operating in this source. A peculiar feature in its spectrum is the X-ray domain, which is unusually soft considering its object class. Interestingly, the relatively soft UV and optical spectrum does not extrapolate well to X-rays. To mimic the observed spectral energy distributions (SEDs) during quiescent and flaring periods, we use both a purely leptonic and a hadro-leptonic modeling approach to reproduce four broadband SEDs from various epochs. When taking into account the steep optical-UV spectrum, we find that the hadro-leptonic scenario better explains the SEDs compared to the purely leptonic model. The hadro-leptonic interpretation of the two γ-ray flares suggests that CGRaBS J0211+1051 could be both a potential neutrino emitter and TeV-bright (E > 10 TeV). Thus, it may offer a unique test bed to check for hadro-leptonic contributions to the multimessenger emission in blazar jets.
Online veröffentlicht: 11. Dezember 2025
Gesehen am 18.02.2026